Characteristics of Bumiputera Small and Medium Enterprises (SME) in the Malaysian wooden furniture industry - Jamal, Mohamad Nuramin (2018)
Bumiputera SMEs in furniture industry has their own characteristics, but there is little information about how Bumiputera manage their business especially in furniture industry. The objectives of this study were to identify the problems faced, key characteristics and most important business aspects in Bumiputera furniture SMEs. This study would be useful for Bumiputera entrepreneurs to improve their weaknesses and be aware of their potential as well as useful to government agencies involved in helping Bumiputera entrepreneurs in furniture industry. The method used was a questionnaire survey of 30 Bumiputera furniture SMEs listed by PEKA, which analyzed using frequency and score analysis. The result from this study showed that Bumiputera furniture SMEs has 17 listed characteristics from five main business aspects which were raw material, financial, market, technology and human resource. Market was their biggest weakness, where they faced difficulty to penetrate export market and hence rely on government tender projects. But, they have their own strength, which is their technology. The technology used were mostly advanced machinery, such as CNC machines in Bumiputera furniture SMEs. It is an advantage for Bumiputera furniture SMEs to get government assistance. But the advantages are not equivalent to their weaknesses where they have to improve their market so that Bumiputera furniture SMEs are in line with the development of other industries.